Creating a profile of preferred pattern of response of the form five students of Sekolah Menengah Kebangsaan Labuan (SMKL) in literary prose texts (short stories). - Maimunah Mohd Ali (2005)
This dissertation is concerned with the teaching of literature in English in the Malaysian school system. literature in English is also one of the components tested in the SPM English Examination. literature in the KBSM English language Program means the use of literary texts to help students appreciate both the language and its esthetic values. TIle study focuses on the Form five students of Sekolah Menengah Kebangsaan Labuan (SMKL), Students responded to varieties of literary texts in school. TIlus, it was felt that a profile of the preferred patterns of response to lI""terary prose texts should be empirically established to find out some basis of understanding of the nature of students' responses to given literary prose texts. TIle study also intended at creating a profile of preferred patterns of response of boys and girls of SMKl. TIleoretical framework of creating a profile of preferred patterns of response was based on the Reader Response TIleory and the preferred patterns of response of boys and girls was based on the theoretical framework of the Schema TIleory (Caro/~ 1972). TIle genres employed in this study was the Narrative and Descriptive (short stories ) prose texts. TIle findings of this study would particularly be useful for classroom practitionelS in the contact of facilllating students' learning and enhancing understanding of the nature of students' response to literary prose texts, particularly short stories.